2016
DOI: 10.1080/00223891.2016.1180625
|View full text |Cite
|
Sign up to set email alerts
|

Prioritizing Harm

Abstract: In this study, we examined if a self-report of trait spite, the Spitefulness Scale, retains the same associations with dark personality traits in individuals with severe mental illness. We also examine if reports on the Spitefulness Scale are correlated with observed spiteful behavior in a game developed to offer opportunities for spite. One hundred twenty individuals clinically diagnosed with psychotic spectrum disorders and receiving inpatient treatment at a state hospital participated in this study and comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 20 publications
1
4
0
1
Order By: Relevance
“…We strengthened prior knowledge of the relationship between impulsivity and spite (Rodgers & Dahling, 2018; Zeigler-Hill & Vonk, 2015) and extended what was found among college students to the offender sample (Marcus et al, 2014). Our results are in line with a conceptualization of spiteful behavior as the outcome of a peculiar will to punish others, externalizing the desire with aggressive acts and without adequate foresight (Moyer et al, 2017; Rodgers & Dahling, 2018).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…We strengthened prior knowledge of the relationship between impulsivity and spite (Rodgers & Dahling, 2018; Zeigler-Hill & Vonk, 2015) and extended what was found among college students to the offender sample (Marcus et al, 2014). Our results are in line with a conceptualization of spiteful behavior as the outcome of a peculiar will to punish others, externalizing the desire with aggressive acts and without adequate foresight (Moyer et al, 2017; Rodgers & Dahling, 2018).…”
Section: Discussionsupporting
confidence: 88%
“…Given that “spiteful behavior may often result from a tendency to externalize and a desire to punish others for their perceived transgressions” (Marcus et al, 2014, p. 3), one can expect it to be linked with aggression. Spiteful individuals are characterized by the tendency to prioritize damaging others, even if that means damaging themselves (Moyer et al, 2017). They show low levels of theory of mind, moral values, and remorse (Ewing, Zeigler-Hill, & Vonk, 2016; Marcus et al, 2014; Zeigler-Hill, Noser, Roof, Vonk, & Marcus, 2015) as well as an instrumental use of self-punishment (Marcus et al, 2014; Shabad, 2000).…”
Section: Pn and Aggressionmentioning
confidence: 99%
“…Shame and guilt subscores were used as mediators in the model. The short form has been previously shown to be adequately reliable and valid and to correlate highly with the longer shame ( r = .94) and guilt ( r = .93) subscales (Moyer et al., 2017; Tangney and Dearing, 2002).…”
Section: Methodsmentioning
confidence: 99%
“…Spitefulness is the trait-like tendency to harm oneself to harm others (Marcus et al, 2014). Both clinical (Moyer et al, 2017) and nonclinical (Kimbrough & Reiss, 2012) samples suggest that approximately 25% of people exhibit high levels of spitefulness. Cross-sectional studies have shown that spitefulness is generally associated with antisocial or maladaptive personality traits.…”
Section: Spitefulnessmentioning
confidence: 99%